(untitled) (Research, Society and Development, 2024)
Objective: to analyze the factors associated with molar-incisor hypomineralization in children. Methodology: this is an integrative literature review study with a qualitative approach. For the review, the health databases available in the Scientific Electronic Library Online (SciELO), in the Latin American and Caribbean Health Literature (LILACS) database accessed through the Virtual Health Library (VHL) and in the PubMed database were used. Results: The study identified that molar-incisor hypomineralization is defined as a qualitative development defect of the dental enamel, which necessarily affects one or more permanent molars, but which may or may not involve the incisors. Thus, the structural conditions of the teeth affected by MIH imply in recurring needs for dental treatments and cause biopsychosocial, emotional and aesthetic impacts on the patients’ quality of life. Conclusion: It is concluded that knowledge of the etiological factors can contribute to the identification of children who are more prone to this condition, as well as the establishment of preventive measures, with the aim of avoiding or reducing the possibility of manifestation of the consequences of this enamel defect.